Situated crowdsourcing during disasters: Managing the tasks of spontaneous volunteers through public displays. Issue 102 (June 2017) - Ludwig, Thomas; Kotthaus, Christoph; Reuter, Christian; Dongen, Sören van; Pipek, Volkmar
Abstract: Although emergency services have already recognized the importance of citizen-initiated activities during disasters, still questions with regard to the coordination of spontaneous volunteers and their activities arise. Within our article, we will present a technological approach based on public displays which aims to foster situated crowdsourcing between affected citizens, spontaneous volunteers as well as official emergency services. We will address the research question: How can the situated tasks performed by spontaneous volunteers be supported by the use of public displays during disasters? First we will present the current state of the art with regard to the coordination practices of spontaneous volunteers and emergency services within disaster situations as well as related problems, potentials and specifics of situated crowdsourcing and public displays. To gain insight into actual coordination practices, we conducted an empirical study with 18 different stakeholders involved in disaster management. Based on the literature review and our empirical study, we have derived a technical concept that supports the task and activity management of spontaneous volunteers as well as the coordination both of the demands of affected people and the offers from spontaneous volunteers. We have implemented our concept as the public display application 'City-Share', which provides a robust communication infrastructure and encompasses situated crowdsourcing mechanisms for managing offers and demands of activities on-the-ground. Based on its evaluation with several users, we will discuss our findings with regard to the assignment of tasks on-the-ground and situated crowdsourcing during emergencies. We outline that City-Share can improve a community's disaster resilience, especially when focusing on the kind of collaborative resilience emerging between official stakeholders and spontaneous volunteers or affected citizens at a local level. Highlights: Empirical study on coordination between emergency services and spontaneous volunteers. Concept for situated task and activity management of spontaneous volunteers. Public display application 'City-Share' for situated crowdsourcing on-the-ground. City-Share combines physical presence, comforting words and getting together.